222. Comparison of Outpatient Antibiotic Prescriptions in a High Prescribing State, 2016–2018. (31st December 2020) - Evans, Christopher D; Ouedraogo, Youssoufou; Keaton, Amelia; Staub, Milner
Abstract: Background: About 80% of antibiotic prescriptions are written in outpatient settings. Outpatient antibiotic use (AU) is highest in the Southern United States. Tennessee consistently has one of the highest AU rates in the country. Previous analyses found that 1, 195 prescriptions were filled in Tennessee per 1, 000 total population in 2016. Moreover, 50% of all outpatient antibiotic prescriptions were written by 9.3% of prescribers. We sought to assess Tennessee outpatient antibiotic prescribing trends, comparing 2016 with 2018 data. Methods: The Tennessee IQVIA outpatient antibiotic prescription dataset from January 1 to December 31, 2018 was analyzed and compared to 2016 results. Orally administered antibacterial agents were included. Patients < 20 years old were classified as pediatric. County level population data were obtained from the Tennessee Department of Health. Antibiotic prescription rates were calculated as antibiotics prescribed per 1, 000 population in the specified age group. Analysis was performed using SAS 9.4. Results: The statewide AU rate decreased from 1, 195 in 2016 to 1, 074 in 2018 per 1, 000 population. Consistent with the previous analysis, female patients (1, 288), those over 65 years (1, 459), and those < 2 years (1, 372) had the highest rates of AU in 2018. Lower rates were observed in all age groups in 2018 except for the 3–9 years group. While narrow penicillins and macrolides remain the most frequently prescribed antibiotics, amoxicillin-clavulanate and ciprofloxacin fell out of the top five antibiotics used in adults, and amoxicillin-clavulanate fell out of the top five antibiotics used in pediatrics. Similar to 2016, 9.2% (3, 098) of the providers contributed to 50% of the total prescriptions in 2016, and 2, 090 of the 2, 994 (69.8%) 2016 highest prescribing providers were also among the highest prescribers in 2018. Conclusion: Despite a decline in outpatient antibiotic prescription volume, Tennessee remains one of the nation's highest prescribing states. While a decline in broad spectrum antibiotic prescriptions may indicate a shift to more appropriate usage, these data do not include indication, excluding appropriate use assessment. Identifying and focusing antibiotic stewardship interventions for consistently high prescribers remains a priority for Tennessee. Disclosures: All Authors : No reported disclosures